Current Trends In Seagrass Research In Indonesia (2010-2020) - Anugrah, Septian; Suryanti, Ani; Nevrita, Nevrita (El-Hayah : Jurnal Biologi, 2021)
Seagrass is a higher plant (Anthophyta) that lives and grows immersed in the marine environment. Seagrass provides important ecosystem services include coastal protection, carbon absorption for climate change mitigation, nutrient storage for eutrophication mitigation and shelter for small fish, and high biodiversity conservation efforts for iconic endangered species. The current lack of global attention, therefore seagrass research is important to increase knowledge on a local and national scale. Given the extent of seagrass beds and the length of Indonesia's coastline which ranges 95,181 km, so it still needs to understand seagrass more deeply, because this is very important for conservation and restoration. The purpose of this review article is to comprehensively review research on seagrass in Indonesia in five years that expected to provide a future perspective for seagrass research in Indonesia. In the publication regarding seagrass studies in Indonesia, there are 7 categories of topics discussed, distribution and biology, plant physiology, microbial ecology, fauna, impacts and potential, carbon absorption, and restoration. In general, the focus on seagrass research in Indonesia includes seagrass species, seagrass communities, nutrient cycles in seagrass ecosystems, physiology, and the impact of pollution on seagrass habitats. The results presented in seagrass research in Indonesia are still quite descriptive and lagging when compared to studies that have been carried out in developed countries. The developed countries have developed new methods for seagrass restoration activities to new knowledge about seagrass genetics that has never been disclosed previously.